Supply or demand? Policy makers' confusion in the pesence of hysteresis - Antonio Fatás; Sanjay R. Singh (University of California, Department of Economics, 2022)
Policy makers need to separate between temporary demand-driven shocks and permanent shocks in order to design optimal aggregate demand policies. In this paper we study the case of a central bank that ignores the presence of hysteresis when identifying shocks. By assuming that all low-frequency output fluctuations are driven by permanent technology shocks, monetary policy is not aggressive enough in response to demand shocks. In addition, we show that errors in assessing the state of the economy can be self-perpetuating if seen through the lens of the mistaken views of the policy maker. We show that a central bank that mistakes a demand shock for a supply shock, will produce permanent effects on output through their suboptimal policies. Ex-post, the central bank will see an economy that resembles what they had forecast when designing their policies. The shock is indeed persistent and this persistence validates their assumption that the shock was a supply-driven one. The interaction between forecasts, policies and hysteresis creates the dynamics of self-perpetuating errors that is the focus of this paper.
Keywords: E32; E60; O4; 330; business cycles; hysteresis; Potential Output; Stabilization Policy